THE EFFECT OF HEALTH EDUCATION USING VIDEO AND LEAFLET ON THE PREGNANT WOMEN'S KNOWLEDGE ABOUT PREECLAMPSIA - Ermiati Ermiati; Arien Dwi Puteri; Mira Trisyani Koeryaman (Universitas Padjadjaran, 2021)
There are many causes of maternal mortality, and one of them is preeclampsia, especially in Indonesia. Pregnant women could prevent maternal mortality caused by preeclampsia with understanding the signs and the dangers of preeclampsia. This research aimed to assess the effect health education using video and leaflets on pregnant women's knowledge about preeclampsia. This study was a quasi-experimental study with pretest and posttest without a control group. The respondent did a pretest about preeclampsia and given an intervention and the posttest. The sampling method was quota sampling with 74 respondents. This research provided collected data through questionnaires of knowledge about preeclampsia and education through video or leaflets. The result of the normality test showed normal distribution. Knowledge value of preeclampsia presented in mean and SD (Standard Deviation). The paired average comparison test used a paired sample t-test; meanwhile, the comparison test average unpaired used Independent Sample t-test. The results showed that video and leaflet affected improving pregnant mothers' knowledge about preeclampsia with a p-value of 0.000 <0.05. The work can be seen from the mean before and after being given video education. It has increased from 67,784 to 86,703 and leaflet education, which also increased from 71,135 to 89,514. Videos and leaflets also have the same level of effectiveness in improving maternal knowledge about preeclampsia, with a p-value of 0.854> 0.05. There was an increased level of expertise after the education by video and leaflet on pregnant women about preeclampsia. Besides, the two media also have the same level of effectiveness in improving maternal knowledge about preeclampsia. A suggestion for further research is to use another learning media such as pamphlet, poster, PowerPoint, or flip chart.